RANCANG BANGUN ALAT BANTU AJAR LAPISAN ATMOSFER BERBASIS MULTIMEDIA - Ezrifal Sany; M. Andy Saputra (JURNAL AKADEMIKA)
Subjects of geography is the study of the earth's surface from both inside and outside the earth's surface. In the material layers of the atmosphere will explain natural phenomena that occur on the planet that will be discussed in the multimedia application. Multimedia application system is designed to help teachers who are explaining the subject to make it easier for students to understand the process in the delivery of information. The application is designed to use a combination of drawing, photo and video applications implemented using Macromedia Flash 8, so it will form a perfect look in the learning process.